2022
DOI: 10.3390/e24111609
|View full text |Cite
|
Sign up to set email alerts
|

First-Principle Derivation of Single-Photon Entropy and Maxwell–Jüttner Velocity Distribution

Abstract: This work is devoted to deriving the entropy of a single photon in a beam of light from first principles. Based on the quantum processes of light–matter interaction, we find that, if the light is not in equilibrium, there are two different ways, depending on whether the photon is being added or being removed from the light, of defining the single-photon entropy of this light. However, when the light is in equilibrium at temperature T, the two definitions are equivalent and the photon entropy of this light is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…s o = h o/T b . 36,39 This theoretical result immediately leads to the conclusion that the negative entropy input into the system can be easily computed as…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…s o = h o/T b . 36,39 This theoretical result immediately leads to the conclusion that the negative entropy input into the system can be easily computed as…”
Section: Discussionmentioning
confidence: 89%
“…s ω = ħω / T b . 36,39 This theoretical result immediately leads to the conclusion that the negative entropy input into the system can be easily computed as with Δ E the total energy of the photons that are emitted from the high-temperature blackbody and have been absorbed by the system. Then the total entropy production (including those of the environment and the system) due to the photon emission and absorption can be evaluated as (detailed derivation is referred to Section VI in ESI†)By noting that the above integration also has the mathematical forms like ( X − Y )( e X − e Y ) with X = ln ϕ M + Δ E MA/B / k B T x and Y = ln ϕ A/B , it is easy to prove the above entropy production is non-negative.…”
Section: Thermodynamical Consistency Of the Dynamical Equationsmentioning
confidence: 94%
“…The situation changes in beams of light, where all photons have the same frequency and similar directions [57]. Scully [58] estimated the entropy change of a laser with one additional photon at the threshold and found that the change can easily be as low as 10 −6 k. However, as pointed out by Li et al [59], the definition of single-photon entropy is involved and not unique. At equilibrium, the entropy s of a single monochromatic photon with frequency ω can be argued to be s = hω/T.…”
Section: The Entropy Per Particle In Macroscopic Systemsmentioning
confidence: 99%